Bio-gas production potential of ruminant and non-ruminant animal excreta - DEEPAK BIRADAR and S. P. SACHIN, S. B. JYOTHI, JOHN ABRAHAM (Indian Journal of Animal Production and Management, 2019)
This research work was carried out to evaluate the bio-gas production potential of four different substratesviz. ruminant dung (cattle and goat) and non-ruminant excreta (pig and poultry). The bio-gas productionpotential of non-ruminants excreta was found to be significantly higher than ruminant excreta due to lessfibre content, presence of undigested fermentable carbohydrates (volatile solids) and reduced nitrogencontent. The bio-gas production potential of pig excreta was found to be significantly (P